Glass baking tray with non-stick function and production method thereof

By applying ceramic modified silicone primer and modified topcoat on the glass baking tray, the problem of poor food adhesion and heat conduction performance of glass baking trays is solved, and non-stick, thermal conductivity, wear resistance and antibacterial effects are achieved.

CN119612937AActive Publication Date: 2025-03-14SHANDONG YUNLONG INTELLIGENT TECHNOLOGY DEVELOPMENT CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510152915.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-03-14
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

Glass baking trays are prone to food adhesions during use, which leads to difficulty in cleaning and poor heat conduction performance. Preheating is required to ensure uniform heating.

Method used

By combining the hydroxyl groups on the surface of nano Al2O3 powder with ethoxy groups on the modified silicone resin, a ceramic modified silicone primer has excellent adhesion and thermal conductivity. The epoxy resin was immersed on antibacterial ceramic powder, carbonized, and constructed a porous carbon framework structure, and filled it into polytetrafluoroethylene to obtain a modified topcoat.

Benefits of technology

It realizes the non-stick function of the surface of the glass baking tray, avoids food adhesion, simplifies the cleaning process, and improves the heat conduction performance, so that the baking tray can be heated evenly. At the same time, the combination of ceramic modified silicone primer and modified topcoat enhances the wear resistance and antibacterial properties of the baking tray.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a glass baking tray with a non-stick function and a production method of the glass baking tray, and belongs to the technical field of kitchen utensils, ceramic modified silicon resin primer is obtained by combining hydroxyl groups on the surface of nano Al2O3 powder with ethyoxyl groups on modified silicon resin, and the ceramic modified silicon resin primer has excellent adhesion capacity and heat conduction capacity; the epoxy resin is impregnated on the antibacterial ceramic powder for carbonization, so that adhesion of food and the glass baking tray can be effectively avoided, bacteria breeding on the surface can be inhibited, a carbon skeleton formed by carbonization can effectively disperse stress through a relative slippage mechanism, the wear resistance of the glass baking tray is enhanced, the service life is prolonged, and the phenomenon that when the temperature changes, the glass baking tray is damaged can be avoided. Stress concentration caused by difference of heat conductivity coefficients between the finishing coat and the primer is avoided, so that the glass baking tray is uniformly heated, and the service life is prolonged; many metal frameworks with adsorption capacity are generated on the surface of the modified curing agent in situ, VOC in the glass baking tray production process can be adsorbed, and the influence on the environment is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of kitchen utensils, and particularly relates to a glass baking tray with a non-stick function and a production method thereof. Background Art

[0002] Glass products play a vital role in people's daily lives, especially in the kitchen environment, where glass containers are everywhere. Glass bakeware is widely used in the catering industry because of its non-toxic natural properties and transparent characteristics, which can significantly enhance the visual appeal of food, increase diners' appetite, and make dishes more tempting. However, glass bakeware also has certain limitations during use. Food easily adheres to the surface of the glass bakeware, especially during baking operations. This adhesion phenomenon makes cleaning difficult, which in turn affects the ease of use of glass containers. In addition, compared with metal bakeware, glass bakeware has poor thermal conductivity. Therefore, before formal use, it is usually necessary to preheat for a period of time to ensure that the bakeware can be evenly heated and reach the required cooking temperature.

[0003] The Chinese patent with the announcement number CN108976941B announced a highly wear-resistant non-stick coating specially used for cooking utensils and its preparation method, including a surface coating and a non-surface coating. The coating includes: polytetrafluoroethylene emulsion, bonding resin, wear-resistant resin, pigment, filler and additives. The components of the surface coating and the non-surface coating are consistent, but there are differences in the content of the components. Specifically, the content of bonding resin in the non-surface coating is higher than that in the surface coating. This design is intended to enhance its adhesion to the glass substrate. However, due to the different content of components in the two layers of coating, when heated, the transfer of heat between the coatings will be uneven, which will cause stress concentration. This stress concentration may cause peeling or shedding between the coatings, affecting the overall performance and durability of the coatings. Summary of the invention

[0004] The purpose of the present invention is to provide a glass baking tray with a non-stick function. The hydroxyl group on the surface of nano-Al2O3 powder is combined with the ethoxy group on the modified silicone resin to obtain a ceramic modified silicone resin primer with excellent adhesion and thermal conductivity, which can prevent the primer from being fragile and falling off. The epoxy resin is impregnated on the antibacterial ceramic powder, and then carbonized to construct a porous and relatively flexible carbon skeleton structure on the surface of the antibacterial ceramic powder, which is filled with polytetrafluoroethylene to obtain a modified topcoat. The spatial structure of the carbon skeleton can effectively disperse the stress through a relative slip mechanism when facing stress, thereby solving the problem that when the temperature changes, the stress concentration caused by the difference in thermal conductivity between the topcoat and the primer further causes the coating to peel off.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A method for producing a glass baking tray with a non-stick function, comprising the following steps: Step 1: Add 5-hydroxyisophthalic acid and epichlorohydrin to a reaction kettle, stir for 30-50 minutes at 50-60°C and 400-500r / min, add 50-60wt% potassium hydroxide solution and tetrabutylammonium bromide to the reaction kettle, stir for 24-26 hours at 50-60°C and 400-500r / min, and remove excess epichlorohydrin in the mixture by rotary evaporation to obtain a crude product; extract the crude product with ethyl acetate, wash with deionized water, dry in anhydrous sodium sulfate for 24-26 hours, filter, remove ethyl acetate from the filtrate by rotary evaporation, and purify by column chromatography using dichloromethane as an eluent to obtain a resin intermediate.

[0006] Step 2: Add 3-aminopropylmethyldiethoxysilane, deionized water and tetrahydrofuran into a reaction kettle, heat to 70-80°C and stir at 400-500r / min for 24-26h, add the resin intermediate into the reaction kettle, stir at 70-80°C and 400-500r / min for 10-12h, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dry at 60-80°C for 16-18h to obtain a modified silicone resin.

[0007] Step 3: Add nano Al2O3 powder with a particle size of 18-20nm and deionized water into the reactor, ultrasonicate for 40-60min, stir for 40-50min at 50-60℃ and 400-500r / min, add modified silicone resin powder into the reactor, continue stirring for 10-12h, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dry at 60-80℃ for 16-18h to obtain ceramic modified silicone resin primer.

[0008] Step 4: Add silicon carbide ceramic powder with a particle size of 30-40 μm, sodium citrate and ethylene glycol into the reactor, stir at 40-50°C and 500-600 r / min for 20-30 min, add sodium acetate into the reactor, heat to 80-90°C, continue stirring for 2-3 h, add nano zinc powder into the reactor, continue stirring for 2-3 h, and obtain antibacterial ceramic powder.

[0009] Step 5: Add bisphenol A epoxy resin powder with a particle size of 20-30 μm, methyltetrahydrophthalic anhydride and triphenol into the reactor, stir for 40-60 min at 20-25 ° C and 500-600 r / min, add antibacterial ceramic powder into the reactor, vacuum impregnate for 3-4 hours, filter, wash the filter cake with deionized water 2-3 times, vacuum dry at 60-80 ° C for 1-2 hours, transfer to a muffle furnace, pass nitrogen protection, heat to 350-370 ° C for 2-3 hours, heat to 500-550 ° C for 2-3 hours, cool naturally, filter, wash the filter cake with deionized water 2-3 times, vacuum dry at 60-80 ° C for 1-2 hours, and obtain antibacterial and wear-resistant agent powder; mix the antibacterial and wear-resistant agent powder and polytetrafluoroethylene powder in a mass ratio of 1:3 to obtain a modified topcoat.

[0010] Step six: Add polyetheramine and deionized water into the reactor, stir for 10-12 min at 40-50°C and 400-500 r / min, stir 4-hydroxybutyl vinyl ether, biphenyl dicarboxylic acid and deionized water at 70-80°C and 400-500 r / min for 1-2 h, add ferric sulfate into the reactor, continue stirring and reacting for 5-6 h, add it dropwise into the reactor at a rate of 40-45 drops / min, continue stirring and reacting for 3-4 h, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dry it at 60-80°C for 16-18 h to obtain a modified curing agent.

[0011] Step seven: placing high borosilicate glass in the roller track of the kiln, heating it to 800-850°C to soften it, transferring the softened high borosilicate glass to the baking tray mold, internally hot bending it, cooling it to 40-50°C to obtain a glass substrate, mixing the ceramic modified silicone resin primer and the modified curing agent in a mass ratio of 7:1, spraying them on the glass substrate with a spray gun, the coating thickness is 450-500μm, placing it in a drying oven at 80-90°C for 15-20min, obtaining a primer coating, the thickness of the primer coating is 450-500μm, and then spraying the modified topcoat on the primer coating of the glass substrate with a spray gun, placing it in a drying oven at 80-90°C for 15-20min, and naturally cooling it to obtain a surface coating, the thickness of the surface coating is 350-400μm, heating it to 320-330°C, keeping it warm for 20-25min, and naturally cooling it to obtain a glass baking tray with a non-stick function.

[0012] Furthermore, in step 1, the usage ratio of 5-hydroxyisophthalic acid, epichlorohydrin, potassium hydroxide and tetrabutylammonium bromide is 40-50g:50-60mL:70-80mL:20-30g.

[0013] Furthermore, in step 2, the usage ratio of 3-aminopropylmethyldiethoxysilane, deionized water, tetrahydrofuran and resin intermediate is 15-20 g: 200-300 mL: 30-40 mL: 20-30 g.

[0014] Furthermore, in step three, the usage ratio of nano-Al2O3 powder, deionized water and modified silicone resin powder is 5-6g: 200-300mL: 15-20g.

[0015] Furthermore, in step 4, the usage ratio of silicon carbide ceramic powder, sodium citrate, ethylene glycol, sodium acetate and nano zinc powder is 10-12g: 2-3g: 200-300mL: 12-14g: 20-25g.

[0016] Furthermore, in step five, the dosage ratio of bisphenol A epoxy resin powder, methyltetrahydrophthalic anhydride, triphenol and antibacterial ceramic powder is 20-25g:50-60mL:10-12g.

[0017] Furthermore, in step six, the usage ratio of polyetheramine, deionized water, 4-hydroxybutyl vinyl ether, biphenyl dicarboxylic acid, deionized water and ferric sulfate is 10-12kg: 5-6L: 8-10kg: 10-11kg: 2-3L: 15-20g.

[0018] Beneficial effects of the present invention: 1. The surface of the glass baking tray prepared by the present invention is coated with a modified topcoat, which is based on polytetrafluoroethylene and has very stable chemical properties. It is not easy to form new chemical bonds with proteins, sugar molecules, etc. in food. Therefore, it is not easy for food molecules to react chemically with the coating surface, thereby avoiding adhesion between food and the coating, making the baking tray easy to clean; and the primer coating and surface coating of the glass baking tray are high temperature resistant and stable, can withstand high temperatures without melting and deformation; have excellent thermal conductivity to ensure that the baking tray can be heated evenly; the surface of the glass baking tray has good wear resistance and antibacterial properties, and does not generate a large amount of volatile organic compounds (VOCs) during the production and preparation process.

[0019] 2. The ceramic modified silicone resin primer of the present invention combines the hydroxyl group on the surface of the nano Al2O3 powder with the ethoxy group on the modified silicone resin, so that the nano Al2O3 powder can be evenly dispersed in the modified silicone resin; the silicone resin has excellent adhesion ability, and the silicon-oxygen bond (Si-O-Si) in the silicone resin has a high bond energy, which enables it to form a strong bond with the chemical bond on the surface of the adherend, which can avoid the primer from being fragile and falling off due to the addition of nano Al2O3, and can be more firmly combined with the topcoat, and the nano Al2O3 can increase the thermal conductivity of the glass baking tray.

[0020] 3. The addition of the antibacterial and wear-resistant agent powder of the present invention can significantly improve the wear resistance and antibacterial properties of the surface coating of the glass baking tray. The epoxy resin is impregnated into the surface of the antibacterial ceramic powder and then carbonized. This process constructs a porous carbon layer structure with relatively low hardness on the surface of the antibacterial ceramic powder, which can effectively disperse stress through a relative slip mechanism, avoid stress concentration caused by high temperature or other external forces, reduce crack propagation and coating peeling, thereby further enhancing the wear resistance of the glass baking tray, and overcoming the defects of polytetrafluoroethylene as a topcoat, which is soft and easy to scratch. At the same time, the design also ensures that the baking tray is heated evenly, thereby extending its service life. The spatial structure of the carbon skeleton can avoid the migration of zinc ions wrapped therein to a certain extent, thereby achieving a long-lasting antibacterial effect.

[0021] 4. The surface of the modified curing agent of the present invention generates many metal skeletons with adsorption capacity in situ, which can adsorb VOC to avoid environmental impact. The benzene ring is introduced into the polyetheramine polymer chain through the addition reaction of the vinyl group, and the metal skeleton can further increase the heat resistance of the curing agent, which can better cure the coating and improve the stability and service life of the curing agent. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Example 1: A method for producing a glass baking tray with a non-stick function, prepared by the following steps: S1: Add 40g of 5-hydroxyisophthalic acid and 50mL of epichlorohydrin into a reactor, stir for 30min at 50°C and 400r / min, add 70mL of 50wt% potassium hydroxide solution and 20g of tetrabutylammonium bromide into a reactor, stir for 24h at 50°C and 400r / min, and remove excess epichlorohydrin in the mixture by rotary evaporation to obtain a crude product; extract the crude product with ethyl acetate, wash with deionized water, dry in anhydrous sodium sulfate for 24h, filter, remove ethyl acetate from the filtrate by rotary evaporation, and purify by column chromatography using dichloromethane as an eluent to obtain a resin intermediate.

[0024] S2: 15 g of 3-aminopropylmethyldiethoxysilane, 200 mL of deionized water and 30 mL of tetrahydrofuran were added to a reactor, heated to 70°C and stirred at 400 r / min for 24 h, 20 g of the resin intermediate was added to the reactor, stirred at 70°C and 400 r / min for 10 h, filtered, and the filter cake was washed twice with deionized water and anhydrous ethanol respectively, and dried under vacuum at 60°C for 16 h to obtain a modified silicone resin.

[0025] By reacting epichlorohydrin with the hydroxyl group of 5-hydroxyisophthalic acid, a resin intermediate with an epoxy group is obtained, which is then combined with the amino group on 3-aminopropylmethyldiethoxysilane. The introduction of the benzene ring significantly increases the overall strength of the silicone resin.

[0026] S3: Add 5 g of nano-Al2O3 powder with a particle size of 18-20 nm and 200 mL of deionized water into the reactor, ultrasonicate for 40 min, stir for 40 min at 50°C and 400 r / min, add 15 g of modified silicone resin powder into the reactor, continue stirring for 10 h, filter, wash the filter cake twice with deionized water and anhydrous ethanol respectively, and vacuum dry at 60°C for 16 h to obtain a ceramic modified silicone resin primer.

[0027] The hydroxyl groups on the surface of nano-Al2O3 powder are combined with ethoxy groups to enable it to be evenly dispersed in silicone resin to obtain ceramic-modified silicone resin primer, which enhances the thermal conductivity of the primer when sprayed into a baking tray. The excellent adhesion and softness of silicone resin can avoid the brittleness caused by the addition of ceramics.

[0028] S4: Add 10g of silicon carbide ceramic powder with a particle size of 30-40μm, 2g of sodium citrate and 200mL of ethylene glycol into the reactor, stir at 40℃ and 500r / min for 20min, add 12g of sodium acetate into the reactor, heat to 80℃, continue stirring for 2h, add 20g of nano zinc powder into the reactor, continue stirring for 2h to obtain antibacterial ceramic powder.

[0029] The silicon carbide ceramic powder is carboxylated and combined with the hydroxyl groups on the surface of nano-zinc under hydrothermal conditions, so that the nano-zinc is evenly loaded on the silicon carbide ceramic powder.

[0030] S5: Add 20g of bisphenol A epoxy resin powder with a particle size of 20-30μm, 50mL of methyltetrahydrophthalic anhydride and 10g of triphenol into the reactor, stir at 20℃ and 500r / min for 40min, add 10g of antibacterial ceramic powder into the reactor, vacuum impregnate for 3h, filter, wash the filter cake with deionized water twice, vacuum dry at 60℃ for 1h, transfer to a muffle furnace, pass nitrogen protection, heat to 350℃ for 2h, heat to 500℃ for 2h, cool naturally, filter, wash the filter cake with deionized water twice, vacuum dry at 60℃ for 1h to obtain antibacterial and wear-resistant agent powder; mix the antibacterial and wear-resistant agent powder and polytetrafluoroethylene powder in a mass ratio of 1:3 to obtain a modified topcoat.

[0031] The epoxy resin is impregnated into the antibacterial ceramic powder and carbonized to form a porous, relatively soft carbon skeleton on the surface of the antibacterial ceramic powder. When used as a modified topcoat filler, it can increase the wear resistance of the glass baking tray. The spatial structure of the carbon skeleton can produce relative slip when facing external force, thereby dispersing stress.

[0032] S6: Add 10 kg of polyetheramine and 5 L of deionized water into a reactor, stir for 10 min at 40°C and 400 r / min, stir and mix 8 kg of 4-hydroxybutyl vinyl ether, 10 kg of diphenyl dicarboxylic acid and 2 L of deionized water at 70°C and 400 r / min for 1 h, add 15 g of ferric sulfate into the reactor, continue stirring and reacting for 5 h, add it dropwise into the reactor at a speed of 40 drops / min, continue stirring and reacting for 3 h, filter, wash the filter cake twice with deionized water and anhydrous ethanol respectively, and dry it in vacuo at 60°C for 16 h to obtain a modified curing agent.

[0033] The benzene ring is introduced into the polyetheramine polymer chain through the addition reaction of vinyl to improve the heat resistance of the curing agent. Traditional silicone resin is prone to produce VOC during processing. Many metal skeletons with adsorption capacity are generated in situ on the surface of the modified curing agent, which can adsorb VOC to avoid affecting the environment.

[0034] S7: Place high borosilicate glass in a kiln roller, heat it to 800°C to soften it, transfer the softened high borosilicate glass to a baking tray mold, heat-bend it into shape, cool it to 40°C to obtain a glass substrate, mix the ceramic modified silicone resin primer and the modified curing agent in a mass ratio of 7:1, spray them on the glass substrate with a spray gun, place it in an 80°C drying oven for 15 minutes, and obtain a primer coating with a thickness of 450μm. Then spray the modified topcoat on the primer coating of the glass substrate with a spray gun, place it in an 80°C drying oven for 15 minutes, cool it naturally, and obtain a surface coating with a thickness of 350μm. Heat it to 320°C, keep it warm for 20 minutes, and cool it naturally to obtain a glass baking tray with a non-stick function.

[0035] Example 2: A method for producing a glass baking tray with a non-stick function, prepared by the following steps: S1: 45 g of 5-hydroxyisophthalic acid and 55 mL of epichlorohydrin were added to a reaction kettle, and the mixture was stirred at 55° C. and 450 r / min for 35 min. 75 mL of 55 wt% potassium hydroxide solution and 25 g of tetrabutylammonium bromide were added to the reaction kettle, and the mixture was stirred at 55° C. and 450 r / min for 25 h. The mixture was rotary evaporated to remove excess epichlorohydrin in the mixture to obtain a crude product. The crude product was extracted with ethyl acetate, washed with deionized water, dried in anhydrous sodium sulfate for 25 h, filtered, and the filtrate was rotary evaporated to remove ethyl acetate. The filtrate was purified by column chromatography using dichloromethane as an eluent to obtain a resin intermediate.

[0036] S2: 18 g of 3-aminopropylmethyldiethoxysilane, 250 mL of deionized water and 35 mL of tetrahydrofuran were added into a reactor, heated to 75°C and stirred at 450 r / min for 25 h, 25 g of the resin intermediate was added into the reactor, stirred at 75°C and 450 r / min for 11 h, filtered, the filter cake was washed twice with deionized water and anhydrous ethanol respectively, and dried under vacuum at 70°C for 17 h to obtain a modified silicone resin.

[0037] S3: Add 5.5g of nano-Al2O3 powder with a particle size of 18-20nm and 250mL of deionized water into the reactor, ultrasonicate for 50min, stir for 45min at 55℃ and 450r / min, add 18g of modified silicone resin powder into the reactor, continue stirring for 11h, filter, wash the filter cake twice with deionized water and anhydrous ethanol respectively, and vacuum dry at 70℃ for 17h to obtain a ceramic modified silicone resin primer.

[0038] S4: Add 11g of silicon carbide ceramic powder with a particle size of 30-40μm, 2.5g of sodium citrate and 250mL of ethylene glycol into the reactor, stir at 45°C and 550r / min for 25min, add 13g of sodium acetate into the reactor, heat to 85°C, continue stirring for 2.5h, add 23g of nano zinc powder into the reactor, continue stirring for 2.5h to obtain antibacterial ceramic powder.

[0039] S5: Add 23g of bisphenol A epoxy resin powder with a particle size of 20-30μm, 55mL of methyltetrahydrophthalic anhydride and 11g of triphenol into the reactor, stir for 50min at 23℃ and 550r / min, add 11g of antibacterial ceramic powder into the reactor, vacuum impregnate for 3.5h, filter, wash the filter cake with deionized water twice, vacuum dry at 70℃ for 1.5h, transfer to a muffle furnace, pass nitrogen protection, heat to 360℃ and keep warm for 2.5h, heat to 530℃ and keep warm for 2.5h, cool naturally, filter, wash the filter cake with deionized water twice, vacuum dry at 70℃ for 1.5h, and obtain antibacterial and wear-resistant agent powder; mix the antibacterial and wear-resistant agent powder and polytetrafluoroethylene powder in a mass ratio of 1:3 to obtain a modified topcoat.

[0040] S6: Add 11 kg of polyetheramine and 5.5 L of deionized water into a reactor, stir for 11 min at 45 ° C and 450 r / min, add 9 kg of 4-hydroxybutyl vinyl ether, 10.5 kg of diphenyl dicarboxylic acid and 2.5 L of deionized water, stir and mix at 75 ° C and 450 r / min for 1.2 h, add 18 g of ferric sulfate into the reactor, continue to stir and react for 5.5 h, add it dropwise into the reactor at a speed of 43 drops / min, continue to stir and react for 3.5 h, filter, wash the filter cake twice with deionized water and anhydrous ethanol respectively, and dry it under vacuum at 70 ° C for 17 h to obtain a modified curing agent.

[0041] S7: Place high borosilicate glass in a kiln roller, heat it to 830°C to soften it, transfer the softened high borosilicate glass to a baking tray mold, heat-bend it internally, cool it to 45°C to obtain a glass substrate, mix the ceramic modified silicone resin primer and the modified curing agent in a mass ratio of 7:1, spray them on the glass substrate with a spray gun, place it in a drying oven at 85°C to dry for 18 minutes, and obtain a primer coating with a thickness of 480μm. Then spray the modified topcoat on the primer coating of the glass substrate with a spray gun, place it in a drying oven at 85°C to dry for 18 minutes, cool it naturally, and obtain a surface coating with a thickness of 380μm. Heat it to 325°C, keep it warm for 23 minutes, and cool it naturally to obtain a glass baking tray with a non-stick function.

[0042] Example 3: A method for producing a glass baking tray with a non-stick function, prepared by the following steps: S1: 50 g of 5-hydroxyisophthalic acid and 60 mL of epichlorohydrin were added to a reactor, and the mixture was stirred at 60° C. and 500 r / min for 50 min. 80 mL of 60 wt% potassium hydroxide solution and 30 g of tetrabutylammonium bromide were added to the reactor, and the mixture was stirred at 60° C. and 500 r / min for 26 h. The mixture was rotary evaporated to remove excess epichlorohydrin in the mixture to obtain a crude product. The crude product was extracted with ethyl acetate, washed with deionized water, dried in anhydrous sodium sulfate for 26 h, filtered, and the filtrate was rotary evaporated to remove ethyl acetate. The filtrate was purified by column chromatography using dichloromethane as an eluent to obtain a resin intermediate.

[0043] S2: Add 20 g of 3-aminopropylmethyldiethoxysilane, 300 mL of deionized water and 40 mL of tetrahydrofuran into a reactor, heat to 80°C and stir at 500 r / min for 26 h, add 30 g of the resin intermediate into the reactor, stir at 80°C and 500 r / min for 12 h, filter, wash the filter cake with deionized water and anhydrous ethanol for 3 times respectively, and dry under vacuum at 80°C for 18 h to obtain a modified silicone resin.

[0044] S3: Add 6 g of nano-Al2O3 powder with a particle size of 18-20 nm and 300 mL of deionized water into the reactor, ultrasonicate for 60 min, stir for 50 min at 60°C and 500 r / min, add 20 g of modified silicone resin powder into the reactor, continue stirring for 12 h, filter, wash the filter cake with deionized water and anhydrous ethanol for 3 times respectively, and vacuum dry at 80°C for 18 h to obtain a ceramic modified silicone resin primer.

[0045] S4: Add 12g of silicon carbide ceramic powder with a particle size of 30-40μm, 3g of sodium citrate and 300mL of ethylene glycol into the reactor, stir at 50℃ and 600r / min for 30min, add 14g of sodium acetate into the reactor, heat to 90℃, continue stirring for 3h, add 25g of nano zinc powder into the reactor, continue stirring for 3h to obtain antibacterial ceramic powder.

[0046] S5: Add 25g of bisphenol A epoxy resin powder with a particle size of 20-30μm, 60mL of methyltetrahydrophthalic anhydride and 12g of triphenol into the reactor, stir at 25℃ and 600r / min for 60min, add 12g of antibacterial ceramic powder into the reactor, vacuum impregnate for 4h, filter, wash the filter cake with deionized water 3 times, vacuum dry at 80℃ for 2h, transfer to a muffle furnace, pass nitrogen protection, heat to 370℃ for 3h, heat to 550℃ for 3h, cool naturally, filter, wash the filter cake with deionized water 3 times, vacuum dry at 80℃ for 2h to obtain antibacterial and wear-resistant agent powder; mix the antibacterial and wear-resistant agent powder and polytetrafluoroethylene powder in a mass ratio of 1:3 to obtain a modified topcoat.

[0047] S6: Add 12kg of polyetheramine and 6L of deionized water into a reactor, stir for 12min at 50°C and 500r / min, stir and mix 10kg of 4-hydroxybutyl vinyl ether, 11kg of diphenyl dicarboxylic acid and 3L of deionized water at 80°C and 500r / min for 2h, add 20g of ferric sulfate into the reactor, continue stirring and reacting for 6h, add it dropwise into the reactor at a speed of 45 drops / min, continue stirring and reacting for 4h, filter, wash the filter cake with deionized water and anhydrous ethanol for 3 times respectively, and dry it in vacuo at 80°C for 18h to obtain a modified curing agent.

[0048] S7: Place high borosilicate glass in a kiln roller, heat it to 850°C to soften it, transfer the softened high borosilicate glass to a baking tray mold, heat-bend it into shape, cool it to 50°C to obtain a glass substrate, mix the ceramic modified silicone resin primer and the modified curing agent in a mass ratio of 7:1, spray them on the glass substrate with a spray gun, place it in a 90°C drying oven and dry it for 20 minutes to obtain a primer coating with a thickness of 500μm, then spray the modified topcoat on the primer coating of the glass substrate with a spray gun, place it in a 90°C drying oven and dry it for 20 minutes, cool it naturally, obtain a surface coating with a thickness of 400μm, heat it to 330°C, keep it warm for 25 minutes, cool it naturally, and obtain a glass baking tray with a non-stick function.

[0049] Comparative Example 1: Based on Example 3, the modified silicone resin powder in step S3 is replaced with commercially available silicone resin powder of the same mass, and the remaining steps remain unchanged to prepare a glass baking tray with a non-stick function.

[0050] Comparative Example 2: Based on Example 3, the antibacterial and wear-resistant agent powder in step S5 is replaced by the antibacterial ceramic powder in step S4, and the other steps remain unchanged to prepare a glass baking tray with a non-stick function.

[0051] Comparative Example 3: Based on Example 3, the iron sulfate in step S6 is omitted, and the other steps remain unchanged to prepare a glass baking tray with a non-stick function.

[0052] In the embodiments and comparative examples: 3-Aminopropylmethyldiethoxysilane, 5-hydroxyisophthalic acid, epichlorohydrin, potassium hydroxide, graphene oxide powder, polyetheramine, 4-hydroxybutyl vinyl ether, and biphenyl dicarboxylic acid were purchased from Sigma-Aldrich.

[0053] Nano-Al2O3 powder was purchased from Qinghe County Dingze Wear-Resistant Materials Co., Ltd.

[0054] High borosilicate glass was purchased from Henan Yike New Materials Co., Ltd.

[0055] Silicon carbide ceramic powder was purchased from Hebei Ruihuang Metal Materials Co., Ltd.

[0056] Methyltetrahydrophthalic anhydride was purchased from Jinan Runbenxiang Chemical Co., Ltd.

[0057] Triphenol was purchased from Jinan Linsheng Chemical Co., Ltd.

[0058] The glass baking trays prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested for performance, and the results are shown in Table 1: 1. Pencil hardness scratch test: The pencil scratch tester is used to test the hardness of the glass baking tray, and the hardness is calibrated by the coating hardness pencil determination method. First, pencils of different hardness (divided into 13 levels according to industrial standards) are installed on the device, and the pencil is kept at 45° to the surface of the glass baking tray, and then pushed forward at a constant speed, while observing whether the surface of the glass baking tray is scratched by the pencil lead. When the coating is scratched, it means that the hardness of the pencil is greater than the hardness of the coating, otherwise, it means that the hardness of the pencil is lower than the hardness of the coating.

[0059] 2. Adhesion test: Test according to ISO2409 standard to evaluate the adhesion strength of spray coating to glass baking tray.

[0060] 3. Thermal conductivity test: The glass baking trays in different groups are measured using a C-THERMTCI thermal conductivity tester to evaluate the thermal conductivity of the glass baking trays in different groups.

[0061] 4. Volatile organic compound test: Refer to the standard HJ2537-2014 "Technical Requirements for Environmental Labeling Products Water-based Coatings" for testing to evaluate the amount of volatile organic compounds generated during the processing of glass bakeware.

[0062] Table 1 Glass baking tray performance test results

[0063] As can be seen from Table 1, the glass baking tray with non-stick function prepared in Examples 1 to 3 of the present invention has a coating shedding area, adhesion and volatile organic compound content that are significantly lower than those of the comparative example, and a thermal conductivity that is significantly better than that of the comparative example, indicating that the glass baking tray prepared by the present invention has excellent wear resistance, thermal conductivity and environmental protection.

[0064] In Comparative Example 1, the modified silicone resin powder is replaced with commercially available silicone resin powder of the same mass. The surface of the modified silicone resin is grafted with ethoxy groups, which can combine with the hydroxyl groups on the surface of the nano Al2O3 powder, so that it can be evenly dispersed in the modified silicone resin, so that it can better cooperate with the modified silicone resin to increase the heat resistance of the silicone resin, and enhance the thermal conductivity when the primer is sprayed to prepare a baking tray. In addition, the excellent adhesion and softness of the silicone resin can avoid the brittleness caused by the addition of ceramics.

[0065] In Comparative Example 2, the antibacterial and wear-resistant agent powder is replaced with antibacterial ceramic powder. The antibacterial ceramic powder is impregnated with epoxy resin and then carbonized. This process constructs a porous and relatively flexible carbon skeleton structure on the surface of the antibacterial ceramic powder. Without the carbon skeleton structure, the stress cannot be effectively dispersed through the relative slip mechanism, resulting in a low adhesion level, a large detachment area, and a low thermal conductivity.

[0066] In Comparative Example 3, ferric sulfate is omitted, and a metal skeleton with adsorption capacity cannot be generated in situ on the surface of the modified curing agent. The modified curing agent is based on polyetheramine, and a benzene ring is introduced into the polyetheramine polymerization chain through an addition reaction of vinyl, which significantly improves the heat resistance of the curing agent. The metal skeleton generated in situ on the surface can avoid VOCs generated by silicone resin during processing and improve the heat resistance of the curing agent. The metal skeleton generated in situ on the surface can further enhance the heat resistance and improve the stability and service life of the curing agent.

[0067] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0068] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for producing a glass baking tray with non-stick function, characterized in that: The steps include: The high borosilicate glass is placed in a kiln roller, heated to 800-850°C to soften it, the softened high borosilicate glass is transferred to a baking tray mold, hot-bent to form it, cooled to 40-50°C to obtain a glass substrate, a ceramic modified silicone resin primer and a modified curing agent are mixed in a mass ratio of 7:1, sprayed on the glass substrate with a spray gun, the coating thickness is 450-500μm, placed in a drying oven at 80-90°C for 15-20min to obtain a primer coating, the primer coating thickness is 450-500μm, and then the modified topcoat is sprayed on the primer coating of the glass substrate with a spray gun, placed in a drying oven at 80-90°C for 15-20min to dry, naturally cooled to obtain a surface coating, the surface coating thickness is 350-400μm, heated to 320-330°C, kept warm for 20-25min, naturally cooled to obtain a glass baking tray with a non-stick function.

2. The method for producing a glass baking tray with non-stick function according to claim 1, characterized in that: The ceramic modified silicone resin primer is prepared by the following steps: Add nano-Al2O3 powder with a particle size of 18-20 nm and deionized water into a reactor, ultrasonicate for 40-60 min, stir at 50-60°C and 400-500 r / min for 40-50 min, add modified silicone resin powder into the reactor, continue stirring for 10-12 h, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dry to obtain a ceramic modified silicone resin primer; The usage ratio of the nano-Al2O3 powder, deionized water and modified silicone resin powder is 5-6g: 200-300mL: 15-20g.

3. The method for producing a glass baking tray with non-stick function according to claim 2, characterized in that: The modified silicone resin powder is prepared by the following steps: Add 3-aminopropylmethyldiethoxysilane, deionized water and tetrahydrofuran into a reaction kettle, heat to 70-80°C and 400-500r / min and stir for 24-26h, add the resin intermediate into the reaction kettle, stir at 70-80°C and 400-500r / min for 10-12h, filter with suction, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dry to obtain a modified silicone resin.

4. The method for producing a glass baking tray with non-stick function according to claim 3, characterized in that: The usage ratio of the 3-aminopropylmethyldiethoxysilane, deionized water, tetrahydrofuran and resin intermediate is 15-20 g: 200-300 mL: 30-40 mL: 20-30 g.

5. The method for producing a glass baking tray with non-stick function according to claim 3, characterized in that: The resin intermediate is prepared by the following steps: Add 5-hydroxyisophthalic acid and epichlorohydrin to a reaction kettle, stir at 50-60° C. and 400-500 r / min for 30-50 min, add 50-60wt% potassium hydroxide solution and tetrabutylammonium bromide to the reaction kettle, stir at 50-60° C. and 400-500 r / min for 24-26 h, and perform rotary evaporation to remove excess epichlorohydrin in the mixture to obtain a crude product; extract the crude product with ethyl acetate, wash with deionized water, dry in anhydrous sodium sulfate for 24-26 h, filter, remove ethyl acetate from the filtrate by rotary evaporation, and perform column chromatography purification with dichloromethane as an eluent to obtain a resin intermediate.

6. The method for producing a glass baking tray with non-stick function according to claim 5, characterized in that: The usage ratio of the 5-hydroxyisophthalic acid, epichlorohydrin, potassium hydroxide and tetrabutylammonium bromide is 40-50g:50-60mL:70-80mL:20-30g.

7. The method for producing a non-stick glass baking tray according to claim 1, characterized in that: The modified topcoat is prepared by the following steps: Add bisphenol A epoxy resin powder with a particle size of 20-30 μm, methyltetrahydrophthalic anhydride and triphenol into a reactor, stir at 20-25° C. and 500-600 r / min for 40-60 min, add antibacterial ceramic powder into the reactor, vacuum impregnate for 3-4 h, filter, wash the filter cake with deionized water 2-3 times, vacuum dry, transfer to a muffle furnace, pass nitrogen protection, heat to 350-370° C. for 2-3 h, heat to 500-550° C. for 2-3 h, cool naturally, filter, wash the filter cake with deionized water 2-3 times, vacuum dry to obtain antibacterial and wear-resistant agent powder; mix the antibacterial and wear-resistant agent powder and polytetrafluoroethylene powder in a mass ratio of 1:3 to obtain a modified topcoat; The dosage ratio of the bisphenol A epoxy resin powder, methyltetrahydrophthalic anhydride, triphenol and antibacterial ceramic powder is 20-25g: 50-60mL: 10-12g.

8. The method for producing a non-stick glass baking tray according to claim 7, characterized in that: The antibacterial ceramic powder is prepared by the following steps: Add silicon carbide ceramic powder with a particle size of 30-40 μm, sodium citrate and ethylene glycol into a reactor, stir at 40-50°C and 500-600 r / min for 20-30 min, add sodium acetate into the reactor, heat to 80-90°C, continue stirring for 2-3 h, add nano zinc powder into the reactor, continue stirring for 2-3 h, and obtain antibacterial ceramic powder; The usage ratio of the silicon carbide ceramic powder, sodium citrate, ethylene glycol, sodium acetate and nano zinc powder is 10-12g: 2-3g: 200-300mL: 12-14g: 20-25g.

9. The method for producing a glass baking tray with non-stick function according to claim 1, characterized in that: The modified curing agent is prepared by the following steps: Add polyetheramine and deionized water into a reaction kettle, stir at 40-50°C and 400-500 r / min for 10-12 min, stir 4-hydroxybutyl vinyl ether, biphenyl dicarboxylic acid and deionized water at 70-80°C and 400-500 r / min for 1-2 h, add ferric sulfate into the reaction kettle, continue stirring and reacting for 5-6 h, add it dropwise into the reaction kettle at a speed of 40-45 drops / min, continue stirring and reacting for 3-4 h, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dry to obtain a modified curing agent; The usage ratio of the polyetheramine, deionized water, 4-hydroxybutyl vinyl ether, biphenyl dicarboxylic acid, deionized water and ferric sulfate is 10-12kg: 5-6L: 8-10kg: 10-11kg: 2-3L: 15-20g.

10. A glass baking tray with non-stick function, characterized in that: It is prepared by the production method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A high wear-resistant non-stick coating specifically for cookware and its preparation method

    CN108976941B

  • Antibacterial hybrid coating for non-sticking pan and preparation method thereof

    CN105567075A

  • Nonstick glass baking tray and manufacturing method thereof

    CN107973532A

  • Composite materials

    CN109642094A

  • Uniform heat-conducting non-stick pan coating and preparation method thereof

    CN113416474A